Cognição e subtarefas do Timed Up and Go em idosos preservados cognitivamente, com comprometimento cognitivo leve e doença de Alzheimer: um estudo longitudinal - Ferreira, Ana Carolina Gonçalves Vilarinho (2022)
Background: Studies suggest that motor alterations are associated with a higher risk of developing cognitive impairment in the elderly. However, no studies were found in the literature that evaluated over time the relationship between specific cognitive domains and functional mobility, nor how functional mobility can predict changes in the cognitive diagnosis in cognitively preserved elderly people with mild cognitive impairment (MCI) and Alzheimer's disease. Alzheimer's (AD). The Timed Up and Go (TUG) and its subtasks - getting up, walking forward, returning, walking back, and turning to sit - is a test widely used in clinical practice to assess functional mobility in the elderly and allows for the analysis of greater cognitive resources. additional organization and planning during the walk, being challenging when compared to straight-line walking tests. Aims: In this thesis two studies were developed: 1) The first aimed to assess whether the measures of functional mobility of the TUG subtasks in elderly people with different conitive profiles (cognitively preserved, MCI and AD) are related to declines in cognitive domains (attention/orientation, memory, fluency, language, visuospatial skills, and global cognitive performance) after 32 months. 2) The second study aimed to analyze whether functional mobility, assessed by the TUG and its subtasks, predicts changes in the cognitive diagnosis and compared the progression of the cognitive diagnosis of MCI, AD and cognitively preserved after 32 months. Furthermore, it analyzed whether the initial performance of the TUG and its subtasks showed similar characteristics among elderly people who worsened or not in the cognitive diagnosis. Method: The volunteers were evaluated in relation to the cognitive medical diagnosis by a specialized team. Cognitive functions were assessed by the Addebrooke Cognitive Examination – Revised (ACE-R) and Clinical Assessment of Dementia (CDR). Functional mobility was evaluated by TUG, associated with the motion capture system using the Qualisys Track Manager software at two moments: M1 (initial moment evaluated between January and September 2015 and diagnosed as cognitively preserved, MCI or AD) and M2 (after 32 months evaluated between September 2017 and May 2018).Results: These studies showed that the return subtask had a positive relationship with decline in most cognitive domains, except verbal fluency, and total scores of global cognitive functions, as assessed by ACER after 32 months. It was also observed that the initial performance in time and cadence of the TUG, the average speed in the forward gait subtask and the number of steps in the return gait were able to predict changes in the cognitive diagnosis after a period of 32 months. In addition, in this same period, most of the elderly maintained or improved the cognitive diagnosis and this same elderly had a shorter TUG time when compared to the group that had a worsening of the cognitive diagnosis. Conclusions: The cognitive impairment caused by MCI and AD can promote a decline in functional mobility not only in more advanced stages of the disease, but also in pre-dementia stages, such as MCI or mild AD stage. Therefore, a clinical assessment of functional mobility using the TUG and its subtasks can contribute to the understanding of the progress of cognitive changes in elderly people with MCI, AD and cognitively preserved. Thus, health professionals, especially physical therapists, can have a better understanding of the evolution of AD and MCI by developing care strategies to delay the progression of functional mobility and the consequent impact on the lives of these elderly people.